To simplify the expression, we can follow the order of operations (also known as PEMDAS).
First, we simplify the expression within parentheses: 2 minus 6 equals -4.
Next, we square -4: (-4)^2 = 16.
Now, we add 5 to 16: 16 + 5 = 21.
The expression becomes: the sum of 5.5 and 4.3 divided by 4 times 21.
Next, we perform the division: (5.5 + 4.3) ÷ 4 = 9.8 ÷ 4 = 2.45.
Finally, we multiply 2.45 by 21: 2.45 × 21 = 51.45.
Therefore, the simplified expression is 51.45.
Simplify: the sum of 5.5 and 4.3 all divided by the quantity 4 end quantity times the quantity 2 minus 6 end quantity squared plus 5.
1 answer